Chemical etching of a semiconductor surface assisted by single sheets of reduced graphene oxide. (February 2018) - Hirano, Tomoki; Nakade, Kazuki; Li, Shaoxian; Kawai, Kentaro; Arima, Kenta
Abstract: Catalyst-assisted chemical etching is an emerging technology for fabricating a variety of three-dimensional nanostructures on a semiconductor surface for future electronic and optical devices. In contrast to conventional wet etching using noble metals, we performed a fundamental study on the chemical etching of a Ge surface assisted by dispersed sheets of reduced graphene oxide (rGO) in water with dissolved O2 molecules. We found that a monolayer sheet of rGO on Ge does not act as a mask but as a chemical tool that enhances etching under the entire sheet. This is probably caused by the dissociation of adsorbed O2 molecules at the edges of vacancies in an rGO sheet, which leads to the formation of a soluble GeO2 layer. We also propose that the reagents and by-products involved in this etching diffuse along the interface between an rGO sheet and the wall of etched Ge, which we believe is a key for achieving higher etching rates. This study is expected to lead to a nanoscale manufacturing process for semiconductor surfaces free from noble-metal contamination. Graphical abstract: Image 1